You Liar! Attributions of Lying. (September 2021) - Curtis, Drew A.
Language is vastly important in shaping cognitions. The word "liar" is used in a variety of social contexts and deception literature, eliciting numerous images, and is rarely the object of research. Two studies explored how people think of the social cognitive label of "liar." In Study 1, the actor-observer difference in the liar attribution was examined, in how people view their own lying compared to others' lies. Additionally, attitudes and acceptability of self and others' lies were investigated. In Study 2, the liar attribution was examined across various types of lies. Results indicated that people judge others to be more deserving of the liar label than one's self and others lie based on their disposition. Additionally, people held more negative attitudes toward others who lie but were more accepting of others who lie.